Could High Levels of Tissue Polypeptide Specific Antigen, a Marker of Apoptosis Detected in Nonalcoholic Steatohepatitis, Improve after Weight Loss?. Issue 2 (3rd June 2013) - Tarantino, Giovanni; Mazzarella, Claudia; Tarantino, Marianna; Di Minno, Matteo Nicola Dario; Conca, Paolo
Abstract : Background: Tissue Polypeptide Specific antigen has recently been proposed as diagnostic marker of apoptosis in NonAlcoholic SteatoHepatitis. The aim of this study was to validate in patients suffering from NonAlcoholic SteatoHepatitis the clinical utility of this marker after different programs of weight reduction. Methods: Overweight/obese patients with visceral adiposity and liver histology compatible were assigned to a Calorically-Restricted diet ( n = 22), a Calorically-Restricted diet plus EXercise ( n = 19) or No Healthy Life Style (control group, n = 21) for six months. The presence of Body-Weight loss was assessed by a Body Mass Index decrease of at least three points. Serum ALanine aminoTransferase, HOmeostasis Model Assessment method value and Tissue Polypeptide Specific antigen concentrations were determined at time 0, after 3 and 6 months in both the Intervention groups and in the controls' one. Results: In NonAlcoholic SteatoHepatitis patients who obtained Body-Weight reduction, a significant decrease of the serum Tissue Polypeptide Specific antigen values was showed with a clear linear trend across time, P = 0.0001. Decrement of Tissue Polypeptide Specific antigen concentrations best differentiated the Body-Weight loss from the body-weight maintenance in respect to Tissue Polypeptide Specific antigen and HOmeostasis Model Assessment method values. Conclusion: This study support the clinical utility of serum Tissue Polypeptide Specific antigen antigen levels in the follow-up of overweight/obese patients with NonAlcoholic SteatoHepatitis on weight reduction programs.